Effect of temperature on growth and fatty acids profile of the biodiesel producing microalga Scenedesmus acutus - El-Sheekh, Mostafa; Abomohra, Abd El-Fatah; El-Azim, Metwally Abd; Abou-Shanab, Reda (Biotechnologie, agronomie, société et environnement, 2017)
The present study examined the effect of temperature (15, 20, 25, 30, 35 and 40 °C) on biomass, esterified fatty acids content and fatty acid productivity of Scenedesmus acutus. This work aimed to study the effect of variation in temperature on lipid productivity and fatty acid profiles of S. acutus as a feedstock for biodiesel production. The alga was grown under different temperatures and its biomass, as well as fatty acid content and composition, were determined. The maximum growth rate of S. acutus was achieved at 30 °C , but there was no significant difference in biomass productivity at 25 and 30 °C (0.41 and 0.42 g·l-1·d-1), respectively. The highest fatty acid content (104.1 mg·g-1 CDW) was recorded at low temperature (15 °C) and decreased with increasing temperature. As a result of high biomass production, fatty acids productivity showed the highest values (41.27 and 42.10 mg.l-1·d-1) at 25 and 30 °C, respectively. The proportion of saturated and mono-unsaturated fatty acids increased from 13.72 to 23.79% and from 11.13 to 33.10% of total fatty acids when the incubation temperature was raised from 15 to 40 °C, respectively. The increase of temperature from 15 to 40 °C decreased the poly-unsaturated fatty acids from 75.15% to 43.10% of total fatty acids, respectively. The present study concluded that incubation temperature was a critical parameter for quantitative and qualitative fatty acid compositions of S. acutus. In addition, the type and proportion of individual fatty acids, which interfere with biodiesel quality, can be modified using different incubation temperatures in order to meet the biodiesel international standards.